A constrained optimal Rayleigh damping coefficients for structures with closely spaced natural frequencies in seismic analysis. Issue 1 (January 2017) - Pan, DG; Chen, GD; Gao, LL
A constrained optimization method is proposed to determine Rayleigh damping coefficients for the accurate analysis of complex structures. To this end, an objective function was defined to be a complete quadratic combination of the modal errors of a peak base reaction evaluated by response spectral analysis. An optimization constraint was enforced to make the damping ratio of a prominent contribution mode exact. Parametric studies were conducted to investigate the effects of the constraint, the cross term of modes, and weighting factors on the optimization objective. A two-story building and a real-world lattice structure were analyzed under six earthquake ground motions to understand the characteristics and demonstrate the accuracy and effectiveness of the proposed optimization method. Unlike the conventional Rayleigh damping, the optimization method provided an optimal load-dependent reference frequencies that account for varying frequency characteristics of earthquakes around the prominent contribution mode.